A novel technique to produce tubular scaffolds based on collagen and elastin. Issue 5 (12th December 2020) - Rodrigues, Isabella C. P.; Pereira, Karina D.; Woigt, Luiza F.; Jardini, André L.; Luchessi, Augusto D.; Lopes, Éder S. N.; Webster, Thomas J.; Gabriel, Laís P.
Abstract: Tubular polymer scaffolds based on tissue engineering techniques have been studied as potential alternatives for vascular regeneration implants. The blood vessels of the cardiovascular system are mainly fibrous, composed of collagen (Col) and elastin (El), and its inner layer consists of endothelial cells. In this work, Col and El were combined with polyurethane (PU), a biocompatible synthetic polymer, and rotary jet spinning, a new and highly productive technique, to produce fibrous scaffolds. The scaffolds produced at 18 000 rpm presented homogeneous, bead‐free, and solvent‐free fibers. The blend formation between PU‐Col‐El was identified by chemical composition analysis and enhanced the thermal stability up to 324°C. The hydrophilic nature of the scaffold was revealed by its low contact angle. Cell viability of human umbilical vein endothelial cells with the scaffold was proven for 72 hours. The combined strategy of rotary jet spinning with a polymer blend containing Col and El was verified as an effective and promising alternative to obtain tubular scaffolds for tissue engineering on a large‐scale production. Abstract : PU‐Col‐El tubular scaffolds using Rotary Jet Spinning for tissue engineering applications.